Model Belajar Siswa Aktif Dengan Pendekatan Alsak (Al Qur’an, Sains Dan Karakter) Pada Pendidikan Anak Usia Dini Untuk Mewujudkan Generasi Emas Indonesia Tahun 2040 - Winarto Winarto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: The demographic bonus phenomenon that occurred in indonesia needs attention, especially from the goverment to carry out programs that empower human resources. Goverment strategic plan with mandates character education at all levels of education is the appropriate action to improve the quality of human resources. Many experts recommend that character education should be carried out character education from an early age. Therefore, learning in early childhood learning models require references oriented character education. ALSAK (al-Qur’an, science, and character) students’ active approach is the idea of learning-oriented model of character education. This model directs students to learn actively study the Qur’an and its meaning associated with scientific knowledge, and character. Based on the study of theory, learning model supporting the implementation of character education in early childhood. The success of the model of active student learning with ALSAK approach has not been tested empirically so as not to obtain information about the effectiveness of this model. Therefore, it is necessary to test the research in order to obtain full information about the increase of student character ECD by applying this model. Keywords: demographic bonus, early childhood education, active student learning model, ALSAK approach